SIKAP IBU PREMENOPAUSE DALAM MENGHADAPI PERUBAHAN FISIOLOGI PADA MASA MENOPAUSE DI BPS Ny TITIK RAHMAWATI, S.ST DESA LEMINGGIR KECAMATAN MOJOSARI KABUPATEN MOJOKERTO - Hidayah, Nurul; Inayah, Khusnul (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2014)
Menopause is not a disease, and therefore does not require special care, but some of the symptoms associated with it can be solved not only with drugs. Thus, it would be better ifthese menopausal issues clearly known by every Indonesian woman.This type of research his descriptive, while the design of this study is to use observation altechniques. The variable inthis study is the attitude of premenopausal woman facing physiological changes in menopauseperiod. The population in this study was premenopau al women in BPS Ny Titik Rahmawati, S.ST Village Leminggir Kirkcaldy District of Mojokerto regency with a population of 109 people. overall sample is a 86 person sampling probability sampling with samplingtechniques cluster random sampling.Physiological changes during the menopause was concluded that Premenopaus al women age 35-40 years had a negative attitude toward the physical changes of menopause, on average, respondents who had a negative attitude elementary school education were 36 respondents (41.9%) anddid notwork 33 respondents(38 ,4%). Health workers provide health promotion by way of counseling and counseling can improve the quality of health services, able to provide the right information, complete and accurate information about menopause, so it can change a negative attitude into a positive attitude.Keyword : Premenopausal, Menopause